Itsy-bitsy babies - Wild, Margaret, 1948- (Little Hare Books, 2009)
"With charming illustrations and rhythmic text that is perfect for reading aloud, this wonderful story about the things babies love to do will inspire endless fun, as babies always love to read about babies. Descriptions of such familiar activities as playing peek-a-boo, clapping, and banging a drum are accompanied by lively illustrations, and will inspire many imitations."--Amazon.com.